2022
DOI: 10.3389/fimmu.2022.919973
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-18 cytokine in immunity, inflammation, and autoimmunity: Biological role in induction, regulation, and treatment

Abstract: Interleukin-18 (IL-18) is a potent pro-inflammatory cytokine involved in host defense against infections and regulates the innate and acquired immune response. IL-18 is produced by both hematopoietic and non-hematopoietic cells, including monocytes, macrophages, keratinocytes and mesenchymal cell. IL-18 could potentially induce inflammatory and cytotoxic immune cell activities leading to autoimmunity. Its elevated levels have been reported in the blood of patients with some immune-related diseases, including r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(76 citation statements)
references
References 231 publications
4
49
0
Order By: Relevance
“…Our studies have shown that both are significantly dysregulated following BIV infection, which consequently facilitates the establishment of the infection. In addition, this study showed that one of the inflammatory cytokines, IL-18 (18), was downregulated, which also confirms the inhibition of the inflammatory response during BIV infection (Table 4).…”
Section: Discussionsupporting
confidence: 76%
“…Our studies have shown that both are significantly dysregulated following BIV infection, which consequently facilitates the establishment of the infection. In addition, this study showed that one of the inflammatory cytokines, IL-18 (18), was downregulated, which also confirms the inhibition of the inflammatory response during BIV infection (Table 4).…”
Section: Discussionsupporting
confidence: 76%
“…A 3-to-5-year follow-up study in 24 CINCA/NOMID patients treated with anakinra showed the sustained remission in most of the subjects, together with a safety profile, the improvement of physician and patients’ quality of life assessment, as well as the normalization of systemic and organ inflammation, with the exception of bone involvement which did not respond to the therapy ( 121 ). Observational studies in different cohorts of patients confirmed these results with a complete and partial remission rate ranging from 40% up to 100% among different studies ( 70 , 114 , 122 , 123 ). In conclusion, anakinra shows a good safety profile, also in pregnancy ( 124 ), and could prevent and stabilize systemic and organ-specific autoinflammatory damages, including hearing loss in DFN34 patients ( 108 , 114 ).…”
Section: Nlrp3 Inflammasome-directed Therapies For the Treatment Of C...supporting
confidence: 53%
“…During the last years, IL-1b cascade inhibitors -anakinra, canakinumab, rilonacept, -the latter only approved in the US -have been shown to be effective and relatively safe, representing a breakthrough for the therapeutic management of CAPS, which are now currently treatable in both the acute phase than in the long-term maintenance (114, 115) (Table 4). Isolated reports and in vitro studies suggested anti-TNF-a agents as a valuable therapeutic option in CAPS, although they appear inferior compared to IL-1 antagonists in symptoms relief and disease control (120,121) while IL-18 inhibition, a key cytokine released upon inflammasome activation, although promising did not show positive results in preclinical and clinical studies, and currently no FDA approved IL-18 antagonist is available in the clinical practice (122). Due to the pivotal role of the NLRP3 inflammasome in a wide array of autoinflammatory and chronic inflammatory diseases, pharmacologic research of NLRP3 cascade inhibitors is actively growing and many compounds targeting NLRP3 inflammasome and its related pathway are currently investigated, as extensively reviewed by Zahid et al (123).…”
Section: Nlrp3 Inflammasome-directed Therapies For the Treatment Of C...mentioning
confidence: 99%
“…IL-18, a member of the IL-1 family, can induce IFN-γ to exert proin ammatory effects [14,15]. In AD, the function of IL-18 depends on its surrounding cytokine environment.…”
Section: Resultsmentioning
confidence: 99%